First finding of anchialine and submarine cave dwelling brittle stars from the Pacific Ocean, with descriptions of new species of Ophiolepis and Ophiozonella (Echinodermata: Ophiuroidea: Amphilepidida) - Okanishi, Masanori; Fujita, Yoshihisa (Zootaxa, 2018)
Two new species, Ophiolepis cavitata n. sp. and Ophiozonella cavernalis n. sp., are described from the specimens collected in shallow water submarine caves in the Ryukyu Islands, southwestern Japan. Ophiolepis cavitata n. sp. is distinguished from the other congeners in having prominent tubercle-shaped knobs on dorsal arm plates; two sizes of disc scales on the aboral disc, the larger surrounded by 3–8 times smaller disc scales; larger scales concave; radial shields wider than long; a trio of distinct scales present distal to each pair of radial shields; oral shields partly concave; 3 arm spines on proximal portion of the arms. Ophiozonella cavernalis n. sp. is distinguished from the other congeners in having polygonal, uniform size disc scales; oral shields almost as long as wide, shallow concave proximal sides that end in a fairly sharp point medially; arms about 9 times longer than disc diameter; 3 cylindrical arm spines, of which the oral most one is slightly larger than other 2 spines. Ophiozonella cavernalis n. sp. is the second finding of an anchialine-endemic ophiuroid and the first finding from the Pacific Ocean.